Characteristic of Urethral Stone Patients in Tertiary Hospital, East Java - Akmal Fawzi; Paksi Satyagraha; Besut Daryanto (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2022)
Objectives. Urethral stone is uncommon with proportion < 2% of all urinary tract stones. The common symptom is urinary retention. Urethral stone therapy depends on the stone location and size. The aim from this research is to find out characteristic urethral stone patients.Methods. The study was conducted retrospectively by collecting data from Saiful Anwar General Hospital and urology medical records from January 2014-August 2017. There were a total of 59 patients with urethral stones.Results. Fifty nine patients were obtained with mean age 52±13.66 years old. The most common chief complaint is urinary retention in 47 patients (80%) with duration of retention between 1 hour and 3 days. Stone size is 1-2 cm in 36 patients (61%) and the largest stone is 6 cm. Anterior urethral stones were located in naviculare fossa in 24 patients (41%) and treated by dorsal meatotomy and meatoplasty. Posterior urethral stones were in 12 patients (20%) and treated by vesicolithotripsy. Anterior and posterior lubrication procedures have 33% and 60% successful rate. There were 27 patients who underwent vesicolithotripsy for further management. Urethrolitotomy and repair urethra was performed for 6 cm stone size.Conclusions. The most chief complaints are urinary retention in urethral stone patients. Most urethral stones were located in naviculare fossa with dorsal meatotomy and meatoplasty as the leading management of choice.